Pemanfaatan Media Online terhadap Pengembangan Usaha Masyarakat di Kecamatan Kota Bahagia Aceh Selatan - Nelly Junaidi; Khairul Habibikhairul.habibi@ar-raniry.ac.i; Rusnawati; Fatimah (Sadida Islamic Communications and Media Studies, 2024)
This article examines the use of online media for community business development in Kota Bahagia Aceh District. Utilizing Online Media as a sales tool for community business development helps online sellers in Happy City because of Using online media, online sellers can market their business without limits so that online sellers can attract customers more. The aim of this research is to find out to what extent the benefits that Online Media brings to mass businesses in Kota Bahagia District. To answer this problem, the author using field research with qualitative research methods which is descriptive in nature, the data collection technique in this research is by means of observation, interviews, documentation and analysis techniques. Research result shows that the use of online media as a sales tool is very important helping online sellers in Kota Bahagia District, South Aceh market their merchandise. By using Online Media for sellers online in Kota Bahagia District can cover a very large area wide so that sales can reach consumers more, making online sales very effective for done.